Long-term health care savings of preventing child maltreatment - Palusci, Vincent J. (Frontiers in Pediatrics, 2026)
IntroductionWhile the harms child abuse and neglect have long been recognized, a growing body of knowledge has more recently developed about the longer-term harms during adulthood and the effectiveness of prevention programs. Research into the long-term effects of Adverse Childhood Experiences has provided a framework for calculating the potential cost savings for the health care system for reductions in adult chronic disease.MethodsThis community case study analyzed health care costs of chronic disease conditions in adulthood in the U.S. State of Michigan to construct economic models of potential savings after reductions in total Adverse Childhood Experiences scores. National estimates, state-specific incidence data, and projections from the Adverse Childhood Experiences studies were used to calculate the population-based impact and specific costs and adult health care savings.ResultsThis analysis compared projected costs for evidence-based prevention programs (home visiting, newborn head trauma education, and pediatric primary care) and showed that a reduction of one Adverse Childhood Experience resulted in health care savings of more than $128 million annually ($55,816,424–$202,054,506) statewide for adult cancer, diabetes mellitus, heart disease, stroke, and pulmonary diseaseDiscussionBuilding on these analyses, this community case study concluded that the health care savings alone more than justify any costs associated with child maltreatment prevention in the health care system.